An experimental study on bond strength of abaca fiber as natural FRP material. Issue 1 (February 2021) - Saidi, T; Amalia, Z; Hasan, M; Hasanuddin, I; Salvana, W; Akram,
Abstract: The use of fiber reinforced polymer (FRP) has been implemented as an alternative for strengthening and repairing methods. Nowadays, the use of natural material for FRP has been developed in order to minimize the disadvantage effects to nature due to synthetic FRP material and economic reason. In this paper, an experimental study was carried out to evaluate the bond strength of abaca fiber as natural reinforced polymer (NFRP) material in reinforced concrete (RC) beams. The test specimen was a beam that had cross-section area of 100 × 100mm 2 and 300mm length. Single rebar was used in this study with 10mm diameter of rebar. Artificial crack was applied in order to consider the initial crack by using cardboard between the concrete. Two externally bonded strengthened beams with a different type of abaca fiber arrangement, bond length, and thickness were applied on the concrete surface. The test was conducted by applying a tension load on the beam until the specimen reach its failure. The results showed that the bond strength decrease as the bond length becomes longer because the maximum load was almost constant for different bond length. The maximum load was approximately around 4 tf for short and long bond length. The compatibility of abaca fiber and rebar was also monitored. Both abaca fiber and rebar able to stand the load compactly. Abaca fiber composite laminate had a similar trend with rebar at the same location where an artificial crack was made. Furthermore, the arrangement and thickness of the abaca fiber composite laminate affected the results.